A Phospholipase C-Like Protein From Ricinus communis Increases Hydroxy Fatty Acids Accumulation in Transgenic Seeds of Camelina sativa - Aryal, Niranjan; Lu, Chaofu (Frontiers in Plant Science, 2018)
There have been strong interests in producing unusual fatty acids in oilseed crops to provide renewable industrial feedstocks. Results are so far largely disappointing since much lower amounts of such fatty acids accumulate in genetically engineered seeds than in their original natural sources. It has been suggested that the flux of unusual fatty acids through phosphatidylcholine (PC) represents a major bottleneck for high accumulation of such fatty acids in triacylglycerol (TAG). We show here that a phospholipase C-like protein (RcPLCL1) from castor bean, which accumulates nearly 90% of the hydroxylated ricinoleic acid in its seed TAG, increases the amount of hydroxy fatty acids (HFAs) when co-expresses with the fatty acid hydroxylase (RcFAH12) in transgenic seed of Camelina sativa. RcPLCL1 shows hydrolyzing activities on both PC and phosphatidylinositol substrates in our in vitro assay conditions. The PC-PLC activity of the RcPLCL1 may have increased the efficiency of HFA-PC to diacylglycerol conversion, which explains our observation of increased HFA contents in TAG concomitant with decreased HFA in the membrane lipid PC during seed development. Consequently, this may also alleviate the potential detrimental effect of HFA on germination of the engineered camelina seeds. Our results provide new knowledge that will help design effective strategies to engineer high levels of HFAs in transgenic oilseeds.